2017
DOI: 10.5380/biofix.v2i2.54469
|View full text |Cite
|
Sign up to set email alerts
|

FUNGOS ASSOCIADOS À MANCHA FOLIAR EM Eucalyptus benthamii Maiden et Cambage NA REGIÃO SUL DO BRASIL

Abstract: Um dos fatores mais importantes que influenciam no sucesso de plantios florestais é a fitossanidade dos mesmos. Doenças foliares causadas por fungos têm sido frequentemente constatadas em plantios de eucalipto em diversas regiões do Brasil. O objetivo deste trabalho foi avaliar os sintomas e identificar os fungos causadores de mancha foliar em testes de procedência e progênies de Eucalyptus benthamii em três locais na região sul do Brasil. A avaliação foi realizada em São Mateus do Sul (PR), Mafra (SC) e Porto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Its spread to diverse production areas after the discovery of its economic value, showing fast diffusion and the ability to adapt to the most diverse climate conditions, from hot and dry, to humid and cold weather [2]. It presents a wide range of uses, including cellulose production, recovery of degraded areas, forests restoration, oils for pharmaceutical industries, ornamentation, windbreaks, firewood and charcoal production [3,4]. However, among the limiting factors to the crop, phytopathogenic agents, mainly fungi, can be present in different cycle stages, occurring in many places, species and seasons of the year, which can cause considerable reduction in the development and yield of eucalyptus [5].…”
Section: Introductionmentioning
confidence: 99%
“…Its spread to diverse production areas after the discovery of its economic value, showing fast diffusion and the ability to adapt to the most diverse climate conditions, from hot and dry, to humid and cold weather [2]. It presents a wide range of uses, including cellulose production, recovery of degraded areas, forests restoration, oils for pharmaceutical industries, ornamentation, windbreaks, firewood and charcoal production [3,4]. However, among the limiting factors to the crop, phytopathogenic agents, mainly fungi, can be present in different cycle stages, occurring in many places, species and seasons of the year, which can cause considerable reduction in the development and yield of eucalyptus [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several species of the genera Alternaria [28], Colletotrichum [29], Curvularia Silva et al [30] and Pestalotiopsis [31] are reported causing leaf disease on different crops, including forest species. Phomopsis sp.…”
Section: Discussionmentioning
confidence: 99%